Search for the decay of a Higgs boson in the ll gamma channel in proton-proton collisions at root s=13 TeV - Sirunyan,AM; Tumasyan,A; Adam,W; Ambrogi,F; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Eroe,J; Del,Valle AE; Flechl,M; et al. (Journal of High Energy Physics, 2018)
A search for a Higgs boson decaying into a pair of electrons or muons and a photon is described. Higgs boson decays to a Z boson and a photon (H → Zγ → γ, = e or μ), or to two photons, one of which has an internal conversion into a muon pair (H → γγ → μμγ) were considered. The analysis is performed using a data set recorded by the CMS experiment at the LHC from proton-proton collisions at a center-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 35.9 fb−1. No significant excess above the background prediction has been found. Limits are set on the cross section for a standard model Higgs boson decaying to opposite-sign electron or muon pairs and a photon. The observed limits on cross section times the corresponding branching fractions vary between 1.4 and 4.0 (6.1 and 11.4) times the standard model cross section for H → γγ → μμγ (H → Zγ → γ) in the 120–130 GeV mass range of the γ system. The H → γγ → μμγ and H → Zγ →γ analyses are combined for mH =125GeV, obtaining an observed (expected) 95% confidence level upper limit of 3.9 (2.0) times the standard model cross section.